IMPLEMENTASI PENYAMPAIAN SURAT PEMBERITAHUAN PERKEMBANGAN HASIL PENYIDIKAN (SP2HP) OLEH SATRESKRIM KEPOLISIAN RESOR AGAM - Dinata, Irfan Leo (UNES Law Review, 2020)
At the Agam police station the community often feels dissatisfied and reacts to the conduct of investigations conducted by the police because they are considered not transparent and their right to know the progress of the investigation is not fulfilled by the investigator. The implementation of providing information on the progress of the investigation by investigators to the Agres Polres Satreskrim was carried out by giving a notification letter on the Progress of Investigation Results (SP2HP). Identification of problems in public services carried out at Agam District Police, especially Reskrim SP2HP is still written, so the reporter (community) must come directly to Agam Police to find out the follow-up of the investigation conducted by Sat Reskrim and requires a long time. Constraints faced by investigators in the delivery of SP2HP are still weak knowledge of Investigators and Investigators regarding the usefulness of SP2HP publishing and the limited ability of personnel to prepare plans for investigation and investigation of criminal acts in accordance with the SOP of Investigation and Investigation. Support for Facilities and Infrastructures at Agam Police Station is inadequate to conduct investigations and investigations into criminal acts.